2017
DOI: 10.1177/0003319717697883
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Ankle–Brachial Index in Patients Undergoing Percutaneous Coronary Intervention: In-Hospital and 1-Year Outcomes From the SHINANO Registry

Abstract: Concomitant coronary and peripheral artery disease is associated with higher periprocedural and long-term percutaneous coronary intervention (PCI) complication rates. We evaluated in-hospital and 1-year clinical outcomes of patients with low or borderline ankle-brachial indexes (ABIs) undergoing PCIs in the drug-eluting stent era. We divided 1370 SHINANO registry patients into 3 groups-low (ABI ≤ 0.9), borderline (0.9 < ABI ≤ 1.0), and normal (1.0 ≤ ABI < 1.4). During the 1-year follow-up, more PCI-related com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…After applying our predefined inclusion and exclusion criteria, 49 studies were further removed for various reasons. Thus, 9 studies 9,11 17,22 were finally included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After applying our predefined inclusion and exclusion criteria, 49 studies were further removed for various reasons. Thus, 9 studies 9,11 17,22 were finally included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies 9,11 14,17,22 reported the MACE as an outcome measure. As shown in Figure 2, a fixed-effect model was selected because there was no significant between-study heterogeneity ( I 2 = 27.2%, P = .212).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this study showed that ABI, which is simple and cost-effective, can be an important prognostic tool for patients with CAD. Similarly, Hashizume et al [ 13 ] showed that patients with an ab-ABI had a significantly higher incidence of PCI-related complications and a less favorable 1-year prognosis. Our long-term study included data with high credibility from the Korean National Statistical Office.…”
Section: Discussionmentioning
confidence: 97%
“…Commonly, a low ABI (<0.9) is associated with all-cause mortality, cardiovascular mortality, and incidence of major coronary event [ 8 ]. In recent studies, borderline ABI values (0.91 to 0.99) were also a risk factor for CAD, stroke, and mortality [ 12 , 13 ]. However, the clinical impact of a borderline ABI in a population treated with percutaneous coronary intervention has rarely been assessed [ 14 ].…”
Section: Discussionmentioning
confidence: 99%